Low seroprevalence of HIV and syphilis in pregnant women in refugee camps on the Thai-Burma border. - Plewes, K; Lee, T; Kajeechewa, L; Thwin, M; Lee, S; Carrara, V; Nosten, F; Mcgready, R (2008)
SUMMARY: Refugee and migrant populations are considered to be at high risk from sexually transmitted infection (STI) and HIV. Cross-sectional surveys for syphilis and HIV were conducted in antenatal clinics (ANCs) on the Thai-Burmese border. In Mae La refugee camp, the seroprevalence of HIV and syphilis were 0.2% (one of 500) (95% CI 0-1.1) and 0% (0 of 404) (95% CI 0-0.9) in 1997; and 0.4% (two of 500) (95% CI 0.1-1.4) and 0.4% (three of 741) (95% CI 0.1-1.2) in 2005, respectively; syphilis seroprevalence in migrant women in 2005 was 0 (0 of 234) (95% CI 0-1.6). The seroprevalence was lower than that reported from surrounding ANCs for Thai or Burmese women. Focus group discussions with HIV-negative and -positive pregnant refugee women established that aspects of Karen culture and isolation (geographical and political) had a significant protective role from HIV and STI. This survey has resulted in programmatic changes in services to pregnant women in this area.